Mathematics Learning Transformation through MESSI LARI Application: Critical Thinking Educative Game for Elementary Students - Riswari, Lovika Ardana; Ermawati, Diana; Mustofa, Hisbulloh Als (FKIP Universitas Lampung, 2025)
Mathematics Learning Transformation through MESSI LARI Application: Critical Thinking Educative Game for Primary School Students. Critical thinking skill is one of the essential 21st-century skills that plays a crucial role in addressing the complexity of life’s problems. However, students still demonstrate low levels of critical thinking, as they tend to accept information without in-depth analysis. Elementary students are increasingly exposed to gadgets, often losing focus during lessons, relying on memorization rather than analyzing problems, and struggling to understand math questions. Objective: This study aimed to develop a technology-based learning medium to enhance students’ critical thinking skills and to evaluate its validity, effectiveness, and practicality. Method: The Research and Development (R&D) approach was employed using the 4D model: Define, Design, Develop, and Disseminate. The study involved 27 fifth-grade students as subjects at Elementary School 4 Troso. The instruments included validation sheets, test items, and questionnaires. The data analysis used the paired sample t-test and the N-Gain test (to determine the effectiveness of the MESSI LARI application). Findings: First, the validation of the MESSI LARI application reached a mean score of 87% from two experts, classified as very valid. Second, the application reported an adequate effectiveness rate of 71.8% based on pretest and posttest results. Third, student questionnaire responses indicated a practicality score of 86.67%, categorized as very practical. Conclusion: This study confirms that the MESSI LARI application, a Critical Thinking Educational Game, is valid, effective, and practical for use in elementary mathematics learning. Keywords: transformation, elementary mathematics, MESSI LARI application, educative game, critical thinking.